Downstreaming Internet of Things Automation and Digitalization in Superior Melon Cultivation with Greenhouse Technology Through a Sustainable Revolving Fund-Based Farming Business Ecosystem - Dwi Wulandari; Putra Hilmi Prayitno; Abdul Rahman Prasetyo; Fikri Aulia; Fuad Indra Kusuma; Annisaa Hammidah Imaduddina; Andi Basuki; Ari Gunawan; Afis Baghiz Syafruddin (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The Technology and Innovation Dissemination Program in Kedungbanteng Village, Ponorogo Regency, East Java, aims to increase melon farmers' productivity through IoT technology and access to revolving funds. This village is known to produce high-quality melons with export potential, but farmers still face significant challenges. The main problems of partners are the low understanding of modern agricultural technology and limited access to capital. Most farmers still rely on conventional methods, such as manual greenhouses, which hinder production efficiency. The solutions offered include two main approaches. The first is the application of IoT technology in melon cultivation in greenhouses to increase productivity and efficiency. The implementation stages include needs identification, sensor installation, and farmer training. Second, farmers are provided access to revolving funds, accompanied by financial management training and the preparation of sustainable business plans. This program is designed to help farmers obtain capital at affordable interest rates and make adopting new technologies more accessible. The method of implementing the activity includes direct training to farmers on the use of IoT technology and financial management, installation and testing of IoT devices in greenhouses, and technical assistance on an ongoing basis. In addition, assistance is carried out by supervising revolving funds and farming training to ensure optimal implementation. The output targets of this program are an increase in melon productivity by 30% in a year, a reduction in operational costs by 20%, and an increase in farmers' understanding of IoT technology and financial management skills. This program is also expected to increase the greenhouse area and farmers' access to capital.